Respuesta :

Answer:

4 (2y-1)=3y+9

-2y. -2y

4 (1)=1y+9

-1. -1

4=1y+8

÷4. ÷4

0=1y+2

Answer:

y = 2.6

Step-by-step explanation:

in order to solve for y in the equation 4(2y-1) = 3y + 9

we fisrt open the bracket according to BODMAS rule

4(2y-1) = 3y + 9

8y - 4 = 3y + 9

the next strp is to collect the like terms

8y -4 -3y = 9

please note that when ever you are taking a positive number across the equall to sign it changes to negative (-) same thing applies to negative sign it changes to positve(+) respectively

8y-3y = 9 + 4

5y = 13

divide both ides by 5

5y/5 = 13/5

y = 2.6

ACCESS MORE